Temperature Controlled Evolution of Pure Phase Cu9S5 Nanoparticles by Solvothermal Process - Olatunde, Olalekan C.; Onwudiwe, Damian C. (Frontiers in Materials, 2021)
Copper sulphides are one of the most explored semiconductor metal sulphide because of their stoichiometric and morphological dependent optical and electrical properties, which makes them tunable for numerous optoelectronic applications. Stoichiometrically, copper sulphides exist in numerous structures which varies from the copper-rich phase (Cu2S) to the copper-deficient phase (CuS). Within these extreme stoichiometric phases lies numerous non-stoichiometric phases with interesting optical properties. Different solvothermal techniques have been explored for the synthesis of copper sulphides; however, the thermal decomposition of single source precursors provides a facile and tunable route to the synthesis of pure phase copper sulphides of different stoichiometries. In this study, copper(II) dithiocarbamate have been explored as a single source precursor compound to study the evolution of pure phase Cu9S5. Below 240ºC, a mixed phase of CuS and Cu9S5 was obtained, and as the temperature was increased beyond 240 ºC, keeping other reaction condition unchanged, the precursor yielded pure phase of Cu9S5. This phase selectivity at high temperature was attributed to the increased ability of oleylamine (used as solvent) to enhance the evolution of the copper rich phase at high temperature. Optical and morphological studies of the pure phase Cu9S5, showed properties that varied considerably with the temperature of synthesis.